Effects of two forms of experiential pedagogy and learning styles on senior secondary school (SSS) students’ achievement in economics (2019)
A copious amount of studies have been done on ways to improve the teaching of economics in high school, but little in the area of bringing in experiential learning into the economics classroom. The researchers attempted this study to examine the effects of two forms of experiential pedagogy and learning style on students' achievement in economics. Six intact SSS2 economics classes were randomly selected from two randomly chosen local government areas of Ogun State. Three hundred and twenty-five SSS students participated in the study. A pre-test, posttest, control group design with a 3x4 factorial matrix was used for the study. The instrument used was an Economics Achievement Test (EAT); constructed and validated by the researchers using IRT methods (ER 0.87) along with the Kolb Learning Style Inventory (KLSI) version 3.1 (2005) (r= 0.77) to obtain data. Three null hypotheses were tested at 0.005 significance level. Analysis of data was done with ANCOVA. The result revealed a significant main effect of treatment (Experience Debriefing, Experience Dictation and Control) (F (2.300) = 186.699, p < 0.05 (0.000), partial ղ=. 554) on students' achievement in economics. To assess where the observed significance lies, bonferonni pair-wise comparison was conducted. The outcome showed that experience debriefing fostered students' achievement in economics most, followed by experience dictation, then control. The result also revealed no significant main effect of learning style on achievement in economics (F (3.300) = 0.943, p>0.05(0.420), partial ղ=.009). In addition, the study revealed no significant interaction effect of teaching method and learning style on students' achievement, (F(6300) = 1.245, p>0.05(0.283)).The researchers concluded that experiential learning approaches are effective and recommend that high school economics teachers should embrace this technique. In addition, they should note the diverse learning needs of students, and use it to plan their lessons.